Hypoxic Training in Obese Mice Improves Metabolic Disorder - Wang, Ru; Guo, Shanshan; Tian, Haili; Huang, Yiru; Yang, Qin; Zhao, Kewei; Kuo, Chia-Hua; Hong, Shangyu; Chen, Peijie; Liu, Tiemin (Frontiers in Endocrinology, 2019)
Hypoxic training has been reported to lower obesity morbidity without clear underlying mechanisms. This study investigates the effect of hypoxic training on metabolic changes, particularly liver metabolism of high fat diet (HFD)-induced obese mice. We compared the hypoxic training group with normoxic sedentary, normoxic training and hypoxic sedentary groups. Body weight, fat mass, glucose tolerance and liver physiology were determined after 4 weeks intervention. In both normoxic training and hypoxic training groups, body weight was lower than the normoxic sedentary group, with less fat mass. Insulin sensitivity was improved after hypoxic training. Moreover, liver metabolomics revealed insights into the protective effect of hypoxic training on HFD-induced fatty liver. Taken together, these findings provide a molecular metabolic mechanism for hypoxic training.